Guests of Honor, Pendet Dance, and the Stage of Honor: Power Struggles in Indonesian Political Culture - I Nyoman Wijaya; Sri Lestari; I Kadek Surya Jayadi (International Journal of Multidisciplinary Sciences, 2026)
The reception of US President Joe Biden with a Pendet dance performance at the 2022 Bali G20 Summit appears to be an ordinary ceremonial event. However, from a post-structuralist historical perspective, it marks his treatment as a formal guest of honor. This protocol mirrors President Sukarno’s state visits in the early 1960s, though Biden was welcomed directly at the airport while Sukarno was received both at the airport and on a public stage of honor in downtown Denpasar. This study traces the historical trajectory of such state receptions, revealing that utilizing a stage of honor has roots spanning the royal era, the Dutch colonial period, and the New Order era, particularly within the Bali Arts Festival (PKB) since 1979. Methodologically, the research relies on oral history, archival studies, and literature reviews.  Theoretically, it frames the analysis using Foucault’s concepts of discontinuity and power-knowledge relations, postcolonialism, and Bourdieu’s practice theory. The study concludes that the stage of honor has undergone a profound functional shift, evolving from a traditional welcoming ritual, political legitimation tool, and tourism commodity into a potent symbol of contemporary political representation.